Surface-initiated Cu(0) mediated controlled radical polymerization (SI-CuCRP) using a copper plate1. Issue 14 (14th April 2015) - Zhang, Tao; Du, Yunhao; Müller, Felix; Amin, Ihsan; Jordan, Rainer
<x xml:space="preserve">Abstract</x> We report on a new, extremely fast, very simple and versatile method to produce polymer brushes by surface-initiated controlled/living radical polymerization.